Deteksi Dini Gangguan Mental Emosional pada Remaja: Sebuah Tinjauan Literatur - Ike Nurhidayah; Zulfa Nurfadhilah Ardalia Putri; Noval Andra Alvido; Sofia Maharani; Hana Pratiwi; Rizki Novirson (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Emotional mental health in adolescents is an important focus because this age group is highly vulnerable to academic and social pressures, as well as the demands of personal development. Emotional problems such as anxiety, stress, and depression that are not recognized early on can interfere with concentration, social relationships, and psychological well-being. This study aims to review the literature related to the early detection of emotional mental disorders in adolescents, so that it can serve as a basis for the development of prevention and intervention strategies. The method used is a literature review, analyzing a number of recent research articles discussing risk factors, symptoms, and early screening methods using instruments such as the Self Reporting Questionnaire (SRQ) and the Strengths and Difficulties Questionnaire (SDQ). The results of the study show that the most common symptoms include anxiety, fatigue, concentration disorders, and relationship problems with peers in adolescents, as well as academic pressure in students. Early screening has been proven to help identify individuals at risk so that intervention can be carried out more quickly. The use of technology, such as web-based expert systems, can also speed up the screening process and improve the accuracy of assessments. It is recommended that educational institutions and health services be more active in conducting mental health screening, providing promotional education, and designing preventive programs. Further research should use analytical or experimental designs to explore risk factors and the effectiveness of interventions in greater depth.